ECOLOGICAL FACTORS’ IMPACT ON THE CONDITION OF MAUSOLEUM OF KHOJA AHMED YASAWI - Akbasova Amankul Dzhakanovna; Aubakirov Nurimzhan Parzhanovish; Anarbekova Gulchat Dzhumabaevna; Sainova Gaukhar Askerovna (Academic Journal of Physical and Chemical Sciences, 2020)
The article gives the results of experimental and estimated researches on ascertainment of ecological factors’ impact on the condition of mausoleum of Khoja Ahmed Yasawi. Main types of anthropogenic sources, existing near historical monument area were detected. Chemically polluted precipitation was determined as the main source of air pollution, generated due to burning of fossil fuel, tires and various waste, accumulation of domestic, construction and other production wastes, transport emissions. It was ascertained that black dust, greenhouse and ozone depleting gas, aerosols of acid, salt, hydrocarbon and its derivatives, heavy metals constitute a special hazard for conservation of mausoleum and its facilities. Vegetation, especially a locust tree was selected for creation of barrier on the spread of corrosive dust and gas mixtures as absorbents. It is planted along conservation zone border. We developed the understratum of new composition to plant the locust tree due to absence of fertile layer in the nekrozem. It represents a mixture of mass. %: vermitea (20), sawdust (20), grey perlite containing waste (5), wood ash (1), the rest is sierozem (nekrozem).